Maintenance of B cells during chronic murine Trypanosoma brucei gambiense infection. (28th July 2016) - Cnops, J.; Kauffmann, F.; De Trez, C.; Baltz, T.; Keirsse, J.; Radwanska, M.; Muraille, E.; Magez, S.
Summary: African trypanosomosis is a debilitating parasitic disease occurring in large parts of sub‐Saharan Africa. Trypanosoma brucei gambiense accounts for 98% of the reported HAT infections and causes a chronic, gradually progressing disease. Multiple experimental murine models for trypanosomosis have demonstrated inflammation‐dependent apoptosis of splenic follicular B (FoB) cells and the destruction of B‐cell memory against previously encountered pathogens. Here, we report that during murine infection with a chronic T. b. gambiense field isolate, FoB cells are retained. This coincided with reduced levels of IFN‐γ and TNF‐α during the acute phase of the infection. This result suggests that in chronic infections with low virulent parasites, less inflammation is elicited and consequently no FoB cell destruction occurs.